The nanophotonic crystals of anodic alumina deposited on InGaN/GaN quantum well structures - Jae, H.C.; Woo, Deok Ha; Jung, Mi; Keunjoo, K. (2006 IEEE Nanotechnology Materials and Devices Conference, NMDC, 2006)
Two-dimensional photonic crystals were fabricated by a two-step anodization of the deposited Al layer on p-GaN surface of InGaN/GaN multi-quantum-well light-emitting-diode structures. Alumina hole arrays with nanometer-scale dimensions enhance the photoluminescence intensity up to three times. The GaN photonic crystals formed by dry etching process also provide the enhancement of light extraction.